2019
DOI: 10.1155/2019/7640547
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Peroxidase 1 Promotes NSCLC Resistance to Cisplatin via ROS-Induced Activation of PI3K/AKT Pathway

Abstract: Purpose. Reactive oxygen species (ROS)-induced cytotoxicity is an important mechanism by which cisplatin kills tumor cells. Glutathione peroxidase family (GPXs) is an important member of antioxidant system which metabolizes intracellular ROS and maintains homeostasis of cells. Altered expressions of GPXs enzymes, especially GPX1, have been described in a variety of human cancers. However, their functional roles in cisplatin-based chemoresistance in human malignancies including non-small cell lung cancer have n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 32 publications
(62 reference statements)
1
46
0
Order By: Relevance
“…TAC (total antioxidant capacity) [233,[237][238][239] TAP/TAOP (total antioxidant power/potential) Assessed via FRAP method: Fe III TPTZ + antioxidant → Fe II -TPTZ [230,240,241] TRAP (total radical-trapping antioxidant parameter)…”
Section: Oxidative Potential Found In Literature Key Reaction Referencesmentioning
confidence: 99%
“…TAC (total antioxidant capacity) [233,[237][238][239] TAP/TAOP (total antioxidant power/potential) Assessed via FRAP method: Fe III TPTZ + antioxidant → Fe II -TPTZ [230,240,241] TRAP (total radical-trapping antioxidant parameter)…”
Section: Oxidative Potential Found In Literature Key Reaction Referencesmentioning
confidence: 99%
“…Mitochondrial SOD2 was shown to be highly expressed in ovarian cancer patients and contribute to antitumor therapy resistance [84]. Non-small-cell lung cancer (NSCLC) cells overexpressing GPX1 were resistant to cisplatin-induced ROS through PI3K/AKT pathway activation [85]. In pancreatic cancer cells, GPX4 was shown to be essential for the maintenance of stemness, and PRX1 was required for p38-mediated invasion [86].…”
Section: Mtor-dependent Antioxidant Mechanism In Solidmentioning
confidence: 99%
“…As an important member of the antioxidant enzyme family to metabolize ROS, glutathione peroxidase (GPX), especially GPX1, is widely expressed in a variety of human cancers. Recently, it was reported that GPX1 could promote the resistance of NSCLC cells to cisplatin through ROS-triggered activation of PI3K/AKT signaling [103]. However, in pancreatic cancer, GPX1 could reverse gemcitabine resistance through the AKT/glycogen synthase kinase 3β (GSK3β)/Snail signaling [104].…”
Section: Other Related Metabolismsmentioning
confidence: 99%